The septate junction protein Tetraspanin 2A is critical to the structure and function of Malpighian tubules in Drosophila melanogaster - Beyenbach, Klaus W. (Am J Physiol Cell Physiol, 2020)
Tetraspanin-2A (Tsp2A) is an integral membrane protein of smooth septate junctions in Drosophila melanogaster. To elucidate its structural and functional roles in Malpighian tubules, we used the c42-GAL4/UAS system to selectively knock down Tsp2A in principal cells of the tubule. Tsp2A localizes to smooth septate junctions (sSJ) in Malpighian tubules in a complex shared with partner proteins Snakeskin (Ssk), Mesh, and Discs large (Dlg). Knockdown of Tsp2A led to the intracellular retention of Tsp2A, Ssk, Mesh, and Dlg, gaps and widening spaces in remaining sSJ, and tumorous and cystic tubules. Elevated protein levels together with diminished V-type H(+)-ATPase activity in Tsp2A knockdown tubules are consistent with cell proliferation and reduced transport activity. Indeed, Malpighian tubules isolated from Tsp2A knockdown flies failed to secrete fluid in vitro. The absence of significant transepithelial voltages and resistances manifests an extremely leaky epithelium that allows secreted solutes and water to leak back to the peritubular side. The tubular failure to excrete fluid leads to extracellular volume expansion in the fly and to death within the first week of adult life. Expression of the c42-GAL4 driver begins in Malpighian tubules in the late embryo and progresses upstream to distal tubules in third instar larvae, which can explain why larvae survive Tsp2A knockdown and adults do not. Uncontrolled cell proliferation upon Tsp2A knockdown confirms the role of Tsp2A as tumor suppressor in addition to its role in sSJ structure and transepithelial transport.